LIVING-DINING-KITCHEN (LDK) DESIGN IN INDONESIAN TINY HOUSE BY ACTIVITY TYPOLOGY AND SPATIAL ORGANIZATION ANALYSIS (Jurnal Arsitektur ARCADE, 2026)
The Tiny House (TH) concept has emerged as a potential solution to urban housing constraints in Indonesia. However, spatial design that adequately accommodates user activities remains challenging. This study aims to identify the essential room combination for Indonesian tiny houses based on millennial user preferences (MUP) and to propose an optimal Living–Dining–Kitchen (LDK) layout using activity typology and spatial organization analysis. A mixed qualitative approach was employed, combining literature review, content analysis of social media platforms, and online questionnaires involving over 300 Indonesian millennial respondents. The findings indicate that LDK is the most preferred essential room combination, accommodating core domestic activities such as cooking, dining, family interaction, and leisure. Spatial organization analysis reveals that an optimal LDK layout requires a minimum circulation area of 60%, corresponding to an effective furniture area of approximately 7.16 m² within a 17.92 m² space. Although layouts with lower circulation ratios were favored by users due to compact kitchen configurations, adjustments to furniture dimensions and arrangement are necessary to maintain functional efficiency and psychological comfort. This study contributes to user-centered design strategies for tiny houses in Indonesia and provides practical guidance for spatial planning of compact residential environments.
Keywords: tiny house, living-dining-kitchen (LDK), preferensi pengguna milenial, organisasi ruang, Indonesia.